The Effect of Burnout and Organizational Justice on Quiet Quitting Behavior among Generation Z Employees in Jakarta: The Mediating Role of Work Engagement - Irwin Sukrisno Soegeng; Jeffry Latumahina; Nurzalinar Joesah (Sean Institute, 2026)
This study examines the effects of burnout and organizational justice on quiet quitting among Generation Z employees in Jakarta, with work engagement as a mediating variable. A quantitative approach with a cross-sectional survey design was employed, involving 280 Generation Z employees aged 22–27 years who had worked in formal organizations in Jakarta for at least one year. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model demonstrated satisfactory convergent validity, discriminant validity, and internal consistency reliability. The structural model showed strong explanatory power, with an R² of 0.934 for quiet quitting and 0.714 for work engagement, while Q² values of 0.817 and 0.622 indicated strong predictive relevance. The results revealed that burnout had a positive and significant effect on quiet quitting and work engagement. Organizational justice and work engagement also had positive and significant effects on quiet quitting. Furthermore, work engagement significantly mediated the relationship between burnout and quiet quitting, as well as the relationship between organizational justice and quiet quitting. These findings indicate that burnout, organizational justice, and work engagement are important factors associated with quiet quitting behavior among Generation Z employees. The study highlights the importance of managing employee burnout, strengthening organizational fairness, and understanding employee engagement in developing effective human resource strategies for younger workers.